Cognitive and neuroimaging correlates of financial exploitation vulnerability in older adults without dementia: Implications for early detection of Alzheimer's disease. (September 2022) - Fenton, Laura; Weissberger, Gali H.; Boyle, Patricia A.; Mosqueda, Laura; Yassine, Hussein N.; Nguyen, Annie L.; Lim, Aaron C.; Han, S. Duke
Abstract: Neuropathology characteristic of Alzheimer's disease (AD) begins to accumulate years to decades before cognitive changes are clinically detectable on standard neuropsychological tests. This presents a challenge for early intervention efforts and has spurred research on the identification of behavioral correlates of early neuropathological changes. Recent evidence suggests that financial exploitation vulnerability (FEV) due to impaired decision making may serve as an early behavioral manifestation of AD neuropathology, thereby indicating an increased likelihood for subsequent cognitive decline. An understanding of the underlying mechanisms of FEV is therefore warranted for the identification of individuals at risk for cognitive decline due to AD, and for empowering and protecting older adults vulnerable to financial exploitation. In the current review, we first highlight the devastating consequences of financial exploitation of older adults. We then summarize research on the cognitive, neuroimaging, and neuropathological correlates of FEV in older adults without dementia and propose a theoretical model in which early accumulation of AD pathology manifests as FEV. We conclude with clinical implications and directions for future research. Highlights: Neuropathology may impact brain regions important for financial decision making. Age-related brain changes can increase financial exploitation vulnerability (FEV). FEV in older age may serve as an early warning sign of Alzheimer's Disease.